2020
DOI: 10.1080/26388081.2020.1715256
|View full text |Cite
|
Sign up to set email alerts
|

Chlorella vulgaris: a perspective on its potential for combining high biomass with high value bioproducts

Abstract: The depletion of fossil fuel reserves, concerns over global warming and the high demand for natural functional foods and products have valorized microalgae as an alternative renewable feedstock. Over the past few decades, extensive research has focussed on microalgae, driven by their increasing applications and future potential. Thus, this review reports on one of the most significant pioneer microalgae, Chlorella vulgaris Beyerinck. The value of and prospects for this microalga for various applications are pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(57 citation statements)
references
References 77 publications
5
49
0
3
Order By: Relevance
“…C. vulgaris is an autotrophic alga but it can also be produced under heterotrophic conditions (Kotrbáček et al, 2015;Madeira et al, 2017;Ru et al, 2020). C. vulgaris is a freshwater, unicellular, green alga belonging to the family Chlorellaceae.…”
Section: Vulgaris Microalgae Characterization and Nutritional Propmentioning
confidence: 99%
See 3 more Smart Citations
“…C. vulgaris is an autotrophic alga but it can also be produced under heterotrophic conditions (Kotrbáček et al, 2015;Madeira et al, 2017;Ru et al, 2020). C. vulgaris is a freshwater, unicellular, green alga belonging to the family Chlorellaceae.…”
Section: Vulgaris Microalgae Characterization and Nutritional Propmentioning
confidence: 99%
“…The nutritional composition of C. vulgaris (Table 1) is generally well known The chemical composition of C. vulgaris depends on the strain and culturing environmental conditions like medium nutrients, temperature, light intensity, pH, and salinity (Ru et al, 2020).…”
Section: Vulgaris Microalgae Characterization and Nutritional Propmentioning
confidence: 99%
See 2 more Smart Citations
“…Using large-scale cultivation technology, C. vulgaris and C. pyrenoidosa are prepared as commercial sources for dietary supplements [11]. Studies have shown that Chlorella cells contain a variety of nutrients and bioactive compounds that promote human health and prevent certain diseases [10,12], suggesting that Chlorella-derived natural compounds might provide substitutes for synthetic compounds or drugs. The content of natural compounds in Chlorella differs greatly between culture conditions and Chlorella species [13,14].…”
Section: Introductionmentioning
confidence: 99%